АPPLICATION OF A METHOD OF INSURANCE PROTECTION AT RADIATING POLLUTION IN SLOPE`S ECOSYSTEMS - Кутлахмедов, Ю.; Матвєєва, І.; Петрусенко, В. (Proceedings of National Aviation University, 2012)
The worked out chamber models of typical slope ecosystems allowed to conduct the estimation of collective dose and radiation risks for a population which uses these ecosystems. On this basis the calculation of the expected losses is conducted from the dose loading estimation of collective and individual risks and losses. An algorithm and chart of insurance defence of population are offered for this type of ecosystems. It is shown what an algorithm is offered it is possible to apply for insurance defence people in other types of ecosystems and radiation situations